2015
DOI: 10.1039/c5nr04339e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible thin-film battery based on graphene-oxide embedded in solid polymer electrolyte

Abstract: Enhanced safety of flexible batteries is an imperative objective due to the intimate interaction of such devices with human organs such as flexible batteries that are integrated with touch-screens or embedded in clothing or space suits. In this study, the fabrication and testing of a high performance thin-film Li-ion battery (LIB) is reported that is both flexible and relatively safer compared to the conventional electrolyte based batteries. The concept is facilitated by the use of solid polymer nanocomposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 60 publications
(131 reference statements)
2
38
0
Order By: Relevance
“…Further, existence of various functional groups in GO nano‐sheets and their contribution towards better Li‐ion mobility cannot be over ruled . The observed Li‐ion conductivity values and their unusual trends are in well accordance with the FWHM values obtained from their respective XRD peaks in which crystalline structure of PEO is disturbed on introduction of small amount of GO that assist in better dissolution of salt in polymer matrix and hence finally lead to enhanced ionic conductivity . Further, augmentation of GO concentration leads to decline in ionic conductivity, which may be due to accumulation of excess GO nanosheets that hinders the transport of Li + ions .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Further, existence of various functional groups in GO nano‐sheets and their contribution towards better Li‐ion mobility cannot be over ruled . The observed Li‐ion conductivity values and their unusual trends are in well accordance with the FWHM values obtained from their respective XRD peaks in which crystalline structure of PEO is disturbed on introduction of small amount of GO that assist in better dissolution of salt in polymer matrix and hence finally lead to enhanced ionic conductivity . Further, augmentation of GO concentration leads to decline in ionic conductivity, which may be due to accumulation of excess GO nanosheets that hinders the transport of Li + ions .…”
Section: Resultssupporting
confidence: 68%
“…A 70‐fold increase in conductivity of the electrolyte membrane is achieved at room temperature in presence of 0.6 wt % GO, which is attributed to fast ion transfer at the interface due to interconnected channels and also to layered GO‐intercalated composites. Kammoun et al . has reported the fabrication of a high performance thin‐film Li‐ion battery composed of PEO and GO nanosheets, showing robust mechanical flexibility over 6000 bending cycles and excellent electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%
“…Kammoun et al demonstrated a flexible LIB, which shows a high operating voltage of 4.9 V, an areal capacity of 0.13 mA h cm − 2 and an energy density of 4.8 mW h cm −3 . This flexible LIB was based on the solid polymer composite electrolyte consisted of PEO and 1 wt% GO nanosheets, which was able to afford 6000 bending cycles with high voltage retention of 93% . This work presented a simple method of encapsulating multilayers by a lamination method that is cost‐effective and scalable.…”
Section: Flexible Energy Storagementioning
confidence: 99%
“…To improve further mechanical strengths, the tremendous efforts have been devoted in the field of solid-state electrolytes. [97][98][99][100][101] Although the solid phase of the electrolytes has low ionic conductivity, it shows better mechanical properties with improved stability in comparison to other liquid or gel polymer electrolytes. Choi and co-workers reported an all-solid-state bendable LIB with a high energy density of ≈2.2 × 10 3 µWh cm −3 .…”
Section: Beyond Flexible Libsmentioning
confidence: 99%